3D-printed hand orthotics for the management of spasticity in cerebral palsy - Moscoso-Porras, Miguel (2018)
Cerebral palsy is a highly debilitating disorder that results from brain damage during development or birth. It can cause motor and language disabilities. Spasticity is one common complication of cerebral palsy which makes movement of upper and lower limbs difficult and often causes joint deformities. To manage spasticity, less intrusive recommendations include the use of hand orthotics. However, in resource-constrained areas, orthotics are often unaffordable and poorly constructed. 3D-printed orthotics could provide an innovative solution, as they utilize high precision manufacturing with low-cost materials. The aim of this study is to determine whether 3D printed orthotics are as effective as conventional orthotics at preventing hand deformities in children with cerebral palsy.